THE CONSIDERATION OF ZONING COMPLIANCE ON THE IMPLEMENTATION OF THE FASTRACK NIL IN JOHOR - Ariff, Amirul Haffiz; Suliman, Suhailizan; Sahid, Mohd Shahrizan; Abdullah, Muhaymin Hakim (PLANNING MALAYSIA, 2021)
Under Section 53 of National Land Code 1965, there were lands alienated before the commencement of NLC whereby the titles do not indicate any particular category of land use and express conditions, but instead are stated as ‘Nil’. Therefore, this paper aims to describe the procedure of Fastrack NIL implementation in Johor and its consideration of zoning compliance upon the imposition of land categories and express conditions for land stated as ‘Nil’. Using content analysis and interview with selected respondent using purposive sampling, it is confirmed that the imposition of conditions or land conversion does not need to be in accordance with the zoning compliance. However, this practice is becoming a norm due to the equitable interests held by landowners and taking into account the interest of the state government, thus zoning must be considered in the Fastrack NIL application.